2016
DOI: 10.1016/j.jgeb.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory potential of important phytochemicals from Pergularia daemia (Forsk.) chiov., on snake venom (Naja naja)

Abstract: Pergularia daemia (Forsk.) chiov., is a milk weed of Asclepiadaceae family. In the present study β-sitosterol, β-amyrin, α-amyrin and lupeol were identified in the leaf by GC–MS. Molecular docking studies were performed to evaluate their activities on phospholipase A2 (PLA2) and l-amino acid oxidase enzymes which constituted a rich source in snake venoms (Naja naja). Snake venom Phospholipase A2 with PDB code 1A3D devoid of co-crystallized ligand was extracted from Protein Data Bank. Using Molegro Virtual Dock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This may explain the high affinity of b-sitosterol to COX-2 as well as the intermolecular connections created. 28 …”
Section: Discussionmentioning
confidence: 99%
“…This may explain the high affinity of b-sitosterol to COX-2 as well as the intermolecular connections created. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Carvalho et al (2013) have identified flavonoids, steroids, coumestan, alkaloids, terpenoids (mono-, di-, and triterpenes), and polyphenols as the bioactive components of ethnomedicinal plants, which have been found to inhibit classes of venom PLA2s. These plant metabolites possess proteinbinding and enzyme-inhibiting properties and can neutralize snake venom (Raghavamma et al, 2016). Mourão de Moura et al (2017) have shown the ability of Tannins to precipitate various protein toxins, chelate metal ions and form complexes with metals such as Zn2+ and Ca2+ ions present in snake venom, thereby neutralizing various lethality induced by snake venom, particularly oedema, haemorrhage, hemolytic and coagulant activities.…”
Section: Discussionmentioning
confidence: 99%
“…The GC/MS chromatograms of leaves of P. daemia were found to contain β-sitosterol, α-amyrin, and lupeol as compared with the standard. 27…”
Section: Unsaponifiable Fractionmentioning
confidence: 99%